The Role of Quercetin and Exercise in Modulating Apoptosis and Cardiomyopathy via PI3K/AKT/FOXO3 Pathways in Diabetic Obese Rats - Mojdeh Khajehlandi; Lotfali Bolboli (Cell Journal)
Objective: Quercetin and exercise both have antidiabetic effects through decreasing blood glucose while increasinginsulin sensitivity. Therefore, the present study aimed to investigate the effects of high-intensity interval training (HIIT)and moderate-intensity continuous training (MICT) exercises along with quercetin administration on apoptosis andcardiomyopathy in diabetic obese rats.Materials and Methods: In this experimental study, 35 male Wistar rats [diabetic rats for experimental groups andnormal rats for healthy control (HC)] were divided into seven groups (for each group n=5): HC, diabetic control (DC),diabetic quercetin control (DQC), diabetic HIIT (DHT), diabetic MICT (DMT), DHT with quercetin (DQHT) and DMTwith quercetin (DQMT). The rats were fed a high-fat diet (HFD) for 8 weeks and a low dose of streptozotocin (STZ)was administered to create a model of type 2 diabetes mellitus (T2DM). Eight weeks of HIIT and MICT with or withoutquercetin treatment were performed. Quercetin was used at 15 mg/kg, as a suspension in carboxymethyl cellulose(CMC) at a concentration of 0.5%. One-way analysis of variance with LSD’s post-hoc test with a significant level ofP≤0.05 was used to analyze data.Results: Just 8 weeks of HIIT and MICT protected the protein content of PI3K, AKT, and FOXO3 and caspase-8 (Casp-8) gene expression in heart tissues (P<0.05). Quercetin and both training protocols decreased blood glucose, whileimproving inflammatory markers and the lipid profile (P<0.05).Conclusion: Reduction in blood glucose along with improvements in the inflammatory markers and the lipid profile byquercetin injection may be a promising approach for the development of new antidiabetic medications. In addition, bothtraining protocols showed potentially successful diabetic cardiomyopathy treatments through modulating the FOXO3and PI3K/AKT pathways.